Improving the Ability to Wear Socks in Autistic Children Through Behavior Modification Interventions - Lysandra Hutomo; Primatia Yogi Wulandari (Psikostudia : Jurnal Psikologi, 2023)
Self-care, cleaning, dressing, and eating skills are the basic skills needed by autistic individuals to achieve independence and improve the quality of life. Apart from focusing on improving certain behaviors, interventions for autistic children also have an impact on stress disorders for both autistic children and their families. This study aims to improve the ability to wear socks in autistic children through behavior modification interventions. The subject of this study was a six-year-old boy who was diagnosed with autism. This type of research used Single Subject Research (SSR) with an A-B-A design consisting of baseline 1, intervention, and baseline 2. The techniques of behavior modification intervention used were forward chaining, prompting, and positive reinforcement. The intervention lasted for nine sessions with five trials in each session. The intervention began with two baseline 1 sessions, five intervention sessions, and ended with two baseline 2 sessions. The results showed an increase in the ability to wear socks independently in autistic children through behavior modification interventions. Keterampilan perawatan diri, kebersihan, berpakaian dan makan merupakan seperangkat keterampilan dasar yang dibutuhkan individu autisme untuk mencapai kemandirian dan meningkatkan kualitas hidup. Selain berfokus pada peningkatan perilaku tertentu, intervensi pada anak autis pun berdampak pada pengurangan stress baik bagi anak autis hingga keluarganya. Penelitian ini bertujuan untuk meningkatkan kemampuan memakai kaos kaki pada anak autis melalui intervensi modifikasi perilaku. Subjek pada penelitian ini adalah seorang anak laki-laki berusia enam tahun yang didiagnosis autis. Jenis penelitian ini menggunakan Single Subject Research (SSR) dengan desain A-B-A yang terdiri dari baseline 1, intervensi, dan baseline 2. Teknik dari intervensi modifikasi perilaku yang digunakan adalah forward chaining, prompting, dan positive reinforcement. Intervensi berlangsung selama sembilan sesi dengan lima kali percobaan di setiap sesinya. Intervensi diawali dengan dua sesi baseline 1, lima sesi intervensi, dan diakhiri dengan dua sesi baseline 2. Hasil penelitian menunjukkan adanya peningkatan kemampuan memakai kaos kaki secara mandiri pada anak autis melalui intervensi modifikasi perilaku.